LEGALITY OF THE EXTRADITION TREATY BETWEEN NATIONS ENGAGING COOPERATION IN RELATION WITH CRIME PREVENTION - Komang Okta Setiawan (Ganesha Law Review, 2020)
International agreements can serve as the basis for determining the basis of cooperation between countries, one of the cooperation between the government of the Republic of Indonesia and other countries in the fight against transnational crime is the extradition treaty. The number of criminals who have fled abroad or otherwise make Indonesia held an extradition treaty with several countries. Issues raised is about setting Extradition treaty as well as the legality of the extradition treaty that made Indonesia against countries that do the same job and if the Indonesian state has not made an extradition treaty with that country are preventing the offender. Agreement is said to be valid when both countries approved the agreement by ratifying the agreement in the form of Law. Therefore, the International Agreement in the field of extradition is critical in the implementation of extradition requests, because through the extradition treaty is essentially required that the submission of the perpetrators of criminal acts based on the agreement made between the countries requesting and state required under Article 27 of the Vienna Convention requires that a request for extradition must be met,